IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PDAM DENGAN MENGGUNAKAN UJI STATISTIK (STUDI KASUS : PELANGGAN PDAM-KOTA BENGKULU) - Gusta Gunawan; Wawan Kurniawan; Khairul Amri (Inersia: Jurnal Teknik Sipil, 2019)
The purpose of this study to determine how much the level of customer satisfaction with the services provided by water drinking regional company (PDAM) of Bengkulu City. Customer satisfaction to clean water services, measured in terms of customer perception in the use of clean water, including water pressure, continuity of water, water quality, and service quality. The research was conducted by distributing questionnaires of 100 respondents. Areas studied as a test site is an area which is distributed by PDAM Surabaya unit, which include Distict of Teluk Segara, Distict of Muara Bangkahulu, and Distict of Sungai Serut. Statistical analysis showed that the water quality variables (X2) be a factor greatly influencing the level of customer satisfaction with a coefficient of 0.427 and the water continuity variables (X3) with acoefficient of 0.276. The level of customer satisfaction with the value 2.340, in the category medium level of satisfaction. The conclusion of the research is to increase the level of customer satisfaction so water drinking regional company (PDAM) of Bengkulu City must pay attention to quality and continuity of water.